2020
DOI: 10.3390/dj8020045
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus (HPV) Vaccine Knowledge, Awareness and Acceptance among Dental Students and Post-Graduate Dental Residents

Abstract: Introduction: The recent development of a vaccine that is highly effective against the human papillomavirus (HPV) has been met with widespread clinical and public health professional acceptance. However, social and societal barriers to vaccination may hamper public health efforts to prevent HPV-mediated diseases. Although a few studies have evaluated knowledge or awareness of HPV vaccination among dentists or dental educators, few studies have evaluated the acceptance, knowledge and awareness of HPV vaccinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Although one recent study found that further education and training would improve willingness of dental providers to discuss and recommend HPV vaccination, previous work from the same group found dental knowledge, awareness and willingness may be more malleable than established dental providers [14][15][16]. It was also found that the awareness among dental students was comparatively lesser than postgraduate students which may be due to the increased experience according to Mann et al ' [13]. In a study conducted by Tan et al and Rashwan et al , it was found that most of the students had a positive attitude towards HPV vaccination as they were aware of cervical cancer and its prevention which was found to be contradictory to the present age [17,18 to the results of the present study, it was found that refusal for vaccination was lack of knowledge among students and efficacy of the vaccine raised doubts due to its increased cost in various other studies [18][19][20][21].…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Although one recent study found that further education and training would improve willingness of dental providers to discuss and recommend HPV vaccination, previous work from the same group found dental knowledge, awareness and willingness may be more malleable than established dental providers [14][15][16]. It was also found that the awareness among dental students was comparatively lesser than postgraduate students which may be due to the increased experience according to Mann et al ' [13]. In a study conducted by Tan et al and Rashwan et al , it was found that most of the students had a positive attitude towards HPV vaccination as they were aware of cervical cancer and its prevention which was found to be contradictory to the present age [17,18 to the results of the present study, it was found that refusal for vaccination was lack of knowledge among students and efficacy of the vaccine raised doubts due to its increased cost in various other studies [18][19][20][21].…”
Section: Resultsmentioning
confidence: 92%
“…1. Percentage of response agreed vaccines were effective (~97%), significantly fewer dental students agreed they were safe [13]. Although one recent study found that further education and training would improve willingness of dental providers to discuss and recommend HPV vaccination, previous work from the same group found dental knowledge, awareness and willingness may be more malleable than established dental providers [14][15][16].…”
Section: Resultsmentioning
confidence: 99%
“…[ 28 30 ] Recent evidence suggests that providing HPV-specific educational resources may improve both knowledge and likelihood of recommending HPV immunization in patient care. [ 31 33 ]…”
Section: Introductionmentioning
confidence: 99%
“…Recent systematic reviews and meta-analyses have shown convincing evidence of significant reductions in HPV infections in geographical areas with increased vaccination, which will possibly facilitate both clinical protection and herd immunity within that population 6 . The World Health Organization (WHO) has necessitated the global elimination of oral and cervical cancer as it is preventable with a well-known etiological factor.…”
Section: Introductionmentioning
confidence: 99%
“…Only a small number of studies have evaluated the familiarity, understanding, and acceptance of HPV vaccination among undergraduate dental students, post-graduate residents, and practitioners. These studies have evaluated and found deficiencies in both knowledge and awareness among dental students specifically, that may be added to the dental curriculum 6 . This study was a prospective analysis of a questionnaire collected from the dentist and dental students at The Faculty of Dental Sciences, Sri Ramachandra Institute of Higher Education and Research, Porur, Chennai, Tamilnadu, India; regarding their knowledge, awareness and vaccination status.…”
Section: Introductionmentioning
confidence: 99%